Hsieh Liang-tso and the Analects of Confucius : Humane learning as a religious quest - Selover, Thomas Whitfield (American Academy of Religion academy series., 2005)
Hsieh Liang-tso (c.1050-c.1120, known as master Shang-ts'ai) was one of the leading direct disciples of Ch'eng Hao and Ch'eng I, the two brothers who were the early leaders of the Confucian revival known as Neo-Confucianism in Northern Sung China. Hsieh was thus among the first to recognize and follow the insights of the Ch'eng brothers as definitive of the authentic Confucian tradition, a recognition that became the conviction of the majority of later Confucian scholars and practitioners. The present book is a focused analysis of the core value of Confucian thought, namely jen (humanity or co.